2006
DOI: 10.1079/bjn20061740
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acetic acid reduces serum cholesterol and triacylglycerols in rats fed a cholesterol-rich diet

Abstract: To investigate the efficacy of the intake of vinegar for prevention of hyperlipidaemia, we examined the effect of dietary acetic acid, the main component of vinegar, on serum lipid values in rats fed a diet containing 1 % (w/w) cholesterol. Animals were allowed free access to a diet containing no cholesterol, a diet containing 1 % cholesterol without acetic acid, or a diet containing 1 % cholesterol with 0·3 % (w/w) acetic acid for 19 d. Then, they were killed after food deprivation for 7 h. Cholesterol feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(158 citation statements)
references
References 41 publications
5
144
1
8
Order By: Relevance
“…Th is eff ect is most probably consequence of observed up-regulation of liver LDL receptor expression aft er PH. It suggests the eff ort of remnant hepatocytes to use LDL cholesterol, mainly in rats of CHOL groups which is in accordance with the results of other authors (21,22 3. We evaluated DNA synthesis as the marker of liver regeneration.…”
Section: Sld Cholsupporting
confidence: 82%
“…Th is eff ect is most probably consequence of observed up-regulation of liver LDL receptor expression aft er PH. It suggests the eff ort of remnant hepatocytes to use LDL cholesterol, mainly in rats of CHOL groups which is in accordance with the results of other authors (21,22 3. We evaluated DNA synthesis as the marker of liver regeneration.…”
Section: Sld Cholsupporting
confidence: 82%
“…Additionally, many studies have reported that acetic acid, the key component of vinegar and contained, exhibits anti-obesity properties and improves lipid metabolism in animal models [17,19,26,27]. However, no study has been performed to compare the anti-obesity effects of spirit vinegar and natural fermented vinegar in rats.…”
mentioning
confidence: 97%
“…Kibizu concentrated liquid suppressed accumulation of lipid droplets in 3T3-L1 cells Dietary vinegar reportedly reduces serum total triacylglycerol and cholesterol in rats and human (Fushimi et al 2006(Fushimi et al , 2002Yamashita et al 2007), suggesting that vinegar plays a role in decreasing adipocyte size. We previously showed that the number of small adipocytes increased and that of large adipocytes decreased in adipocyte tissues in Kurozu-treated rats (Tong et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, various types of vinegar are produced by using different sources and technologies (Gullo and Giudici 2008). The main component of vinegar, acetic acid, has various beneficial effects against hyperglycemia (Sakakibara et al 2006), dyslipidemia (Fushimi et al 2006), and hypertension (Kondo et al 2001). Thus, many researchers have focused on vinegars and their functionalities.…”
Section: Introductionmentioning
confidence: 99%